Engineering Model of Economic Institution Insugarcane Agribusiness Partnership (Case Study on Sugar Cane Agribusiness Partnership between Farmers Cooperative and Sugar Factory in Way Kanan Regency of Lampung Province-Indonesia) - Syahril Daud; Adrina Yustitia (Bandar Lampung University, 2015)
The study aims to build the institutional model of sugarcane agribusiness and to know the impact of institutional engineering on the performance of sugarcane agribusiness in increasing incomes and welfare of farmers. The research was carried out inWay Kanan regency of Lampung province of Indonesia by using case studies, and the data were analyzed descriptively. The institutional engineering through building a model of farmer groups formation, the combining group of farmers and farmer cooperatives in the autonomous and powerful sugarcane agribusiness will be able to increase the sugarcane agribusiness revenue of Rp11,591,714.00 (increased by 94.33% from the previous income) and cane growers can obtain subsidies and other facilities from the government, sugar factories, a provider of production, access to capitalof the Bank, thus increasing welfare.